2016
DOI: 10.1155/2016/8141658
|View full text |Cite
|
Sign up to set email alerts
|

Estimating Access to Drinking Water Supply, Sanitation, and Hygiene Facilities in Wolaita Sodo Town, Southern Ethiopia, in Reference to National Coverage

Abstract: Introduction. The coverage of sanitation and access to safe drinking water in Ethiopia especially in Wolaita Sodo town are not well studied. Therefore, the main objective of this study was estimating access to drinking water supply, sanitation, and hygiene facilities in Wolaita Sodo town, southern Ethiopia, in reference to national coverage. Methods. A community based cross-sectional study design method was employed in the study in 588 households of Wolaita Sodo town inhabitants. Face-to-face interview to hous… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

7
19
4

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 19 publications
(30 citation statements)
references
References 15 publications
7
19
4
Order By: Relevance
“…This is lower than the study done in Wolaita town 28.5% of the respondents had used chemical disinfection. 23 The study showed that there was a higher water treatment practice in the HH level as compared to EDHS 2005 Report, at which only 8% of the HHs treat water at HH prior to drinking. 27 The result of this study revealed that only 7.7% of the HH use ≥20 litre per capita per day water consumption.…”
Section: Discussionmentioning
confidence: 84%
See 2 more Smart Citations
“…This is lower than the study done in Wolaita town 28.5% of the respondents had used chemical disinfection. 23 The study showed that there was a higher water treatment practice in the HH level as compared to EDHS 2005 Report, at which only 8% of the HHs treat water at HH prior to drinking. 27 The result of this study revealed that only 7.7% of the HH use ≥20 litre per capita per day water consumption.…”
Section: Discussionmentioning
confidence: 84%
“…The physical access of water to the HHs was 74.5% which is higher with study done in Wolaita town (67.9%). 23 This might be the difference of measurement of coverage of water supply that means in the current study we use 1.5km since it is rural community but in Wolaita town access is measured with in 1km radius. The current study was lower than the EDHS 2011 report, 94.5%.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…These lower formal educational levels might in uence the sanitation awareness of the respondents although other sources of knowledge are there. Educational status were signi cantly associated with use of improved water source and sanitation [8,2]. Individuals with High school completed or above educational level demonstrated better latrine utilization than those without formal education [12].…”
Section: Discussionmentioning
confidence: 99%
“…[7] reported a 58.4% latrine coverage for Bahir Dar Zuria District, north western Ethiopia. [8] also reported that about 68% and 95% of the inhabitants of Wolaita Sodo Town (Southern Ethiopia) had access to improved water supply and latrine, respectively. According to [19], 31.2% of respondents of Gonji Kolela Woreda in West Gojjam Zone, northwestern Ethiopia were using either river or unprotected spring for their domestic consumption [9] indicated the possession of latrine by 89% of households in Diretiyara, Eastern Ethiopia.…”
Section: Introductionmentioning
confidence: 99%